(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Analyzing three scenic works that are part of the so-called contemporary circus, the article seeks to contribute to the deepening of knowledge about this way of doing, and about the very representations and practices that support such a classification in circus arts. The analysis and observation categories reside in the intersection zone between the poetic and political dimensions. The scenic works are conceived and performed by women artists or non-binary people, so that the study also touches issues of gender discussion. The research involved field work with interviews with the authors as well as empirical and/or participant observation in the process of creation or other spaces where works have been discussed.